The effects of light curing units and environmental temperatures on CC conversion of commercial and experimental bonding agents - Tahereh Sadat Jafarzadeh-Kashi; Mohmmad Erfan; Salmeh Kalbasi; Malihe Ghadiri; Vahid Rakhshan (Saudi Dental Journal)
Background and purpose: Polymerization of bonding agents (BA) is a critical factor in determining the success of bonded restorations. We aimed to assess the effects of two light curing units and two temperatures on the extent of polymerization (EP) of a commercial BA and an experimental BA. Methods: Forty BA specimens were randomly divided into 8 subgroups of n = 5 to compare the polymerization of two BAs (experimental/Scotchbond) based on the variables: temperature (23/37 °C) and light-curing unit (quartz-tungsten-halogen/light-emitting diode). The EP (%) was measured using differential scanning calorimetry, and analyzed using the t-test, two- and three-way analyses of variance (ANOVA), and the Bonferroni test (α = 0.05). Results: There were significant differences between the EP results between the two BAs (P = 0.012) and due to the different temperatures (P = 0.001), but not between the different light-curing units (P = 0.548). The interaction between BA and temperature was significant (P < 0.001). The other interactions were nonsignificant. Conclusions: The two light-curing units had similar effects on the EP. The EP values were better when curing was performed at human body temperature. Keywords: Extent of polymerization, Bonding agent, Light-curing units, Temperature, Dental materials, Differential scanning calorimetry, Light-curing of dental adhesives, Polymerization